The Influence of Perceived Travel Risk, Celebrity Endorsement, and Destination Image on Attitude and Revisit Intention of Tourists - I Putu Gde Sukaatmadja; I Gusti Ngurah Jaya Agung Widagda; Ni Nyoman Kerti Yasa; Putu Laksmita Dewi Rahmayanti; I Gusti Ayu Tirtayani (International Journal of Asian Business and Management, 2023)
This study aimed to explain how attitudes and revisit intentions are affected by celebrity endorsement, perceived risk of travel, and perception of the destination. The study's participants are domestic travelers who have been to Bali. 170 domestic tourists were included in the sample using a purposive sampling technique. Path Analysis utilizing SEM-PLS is the analysis method employed. The findings demonstrated that attitudes and intentions to revisit were negatively and significantly impacted by perceived travel risk. While celebrity endorsement has no impact on the intention to return, it has a positive and large impact on attitude. Additionally, views and inclinations to return are positively and significantly impacted by the final picture. The image of a destination is positively and significantly impacted by attitudes. thanks to celebrity support Impact on the intention to revisit is favorable and considerable. Because of this, it's critical for companies in the tourism industry to focus on among order to foster a positive attitude among visitors and increase their intention to return to Bali, perceived travel risk, celebrity endorsements, and destination image are used which is increasing